The Use Of Internet In Supplier Selection Process And Managerial Performance In The Northern Region Of Peninsular Malaysia - TONY, LIM SWEE KING (2005)
Cost of material is known to take up a major proportion of the total product cost. In order for manufacturing organizations to maintain competitiveness, having the good support from upstream suppliers is inevitably important. This has made the suppliers selection decision a critical task for purchasing personnel. Fortunately, the internet as an information-rich resource and inter-organizational communication tool, has transformed the way to garner strategic information about prospective suppliers before making the decision on desired partnership.